Impact of harvesting machinery on soil physical parameters : evaluation of ProFor model in three main forestry regions of South Africa - Kachamba, Daud Jones (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScFor (Forest and Wood Science))--University of Stellenbosch, 2007.